Peran Manajemen Sumber Daya Manusia dalam Pembentukan Karakter Guru di Sekolah Islam - Ani Apiyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Human resource management (HRM) in Islamic schools plays a crucial role in shaping the character of teachers, which in turn influences the character development of students. This study aims to analyze the contribution of HRM in enhancing the quality of teachers' character through recruitment, training, and evaluation processes in Islamic schools. A qualitative approach using literature review is employed to analyze theories of HRM and character education. The findings reveal that teacher selection in Islamic schools focuses not only on academic competence but also on moral values and ethics in accordance with Islamic teachings. Ongoing character training helps teachers internalize Islamic values in their daily lives, making them role models for students. Teacher performance evaluations also include character aspects, which are strengthened through a reward system that recognizes the moral and ethical contributions of teachers. In conclusion, effective HRM in Islamic schools produces teachers who are not only academically competent but also of noble character and capable of shaping students' character in line with Islamic values